Effect of Season and Year of Birth on Pubertal Age, Body Weight and Scrotal Circumference of Kankrej Bulls at First Semen Collection - Dangar, Nikhil S; Brahmkshtr, Balkrishna P; Deshmukh, Niteen; Modi, Lalit C; Khasatiya, Chandubhai T; Ramani, Umed V; Kharadi, Vishnu B; Pandya, Gaurav M (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Data on 26 bulls of Kankrej cattle (birth date from 2006 to 2017) inducted at a semen station from 2010 to 2020 were analyzed to studythe effects of season and year of birth on age, body weight and scrotal circumference of bull at first semen collection. The overall leastsquares means for age, body weight, and scrotal circumference of bulls at first semen collection were 1122.36 ± 86.9 days, 537.69 ± 10.51 kg and 30.86 ± 1.60 cm. Non-genetic factors like season and year of birth did not contribute significantly (p>0.05) to these parameters’ variations. Results of the study revealed well adaptation of Kankrej cattle breed to seasonal changes and farm management took care of yearly variation in such a way that age, body weight and scrotal circumference of Kankrej bulls at first semen collection did not vary significantly.
Keywords: Age; Bodyweight; First semen collection; Kankrej; Scrotal circumference; Season of birth